Aplikasi Pupuk Organik Cair Dari Rebung Bambu Pada Tanaman Sawi Manis (Brassica Juncea L) - Yeni Septia Devi; Novilda Elizabeth Mustamu; Dini Hariyati Adam; Hilwa Walida (Jurnal Pengabdian Magister Pendidikan IPA, 2023)
This community service activity is carried out through the use of liquid organic fertilizer made from bamboo shoots. Bamboo shoots are a food ingredient that is quite popular in the community. Impressed with vegetables, bamboo shoots, which are often known as bung (Javanese), have been used by rural people since ancient times as a cooking ingredient, especially for making vegetables. Apart from being used as vegetables, bamboo shoots can be used to make liquid organic fertilizer (POC). In addition, bamboo shoots contain the hormone giberellin, so that they can stimulate plant growth quickly. Because bamboo shoots contain gibberellins, liquid organic fertilizer from bamboo shoots functions to stimulate plant vegetative growth. Therefore efforts are made to increase knowledge in the community so that later it can reduce dependence or farmers on the use of chemical fertilizers.